Complex sexual crime - Sal y Rosas, Federico (1939)
Here is the clinical and psychological observation made by us in the wake of a medical-legal expert. It is a trial for uxoricide, who has symptoms of mental alienation, and whose pre-morbid history highlights events have certainly had important role in the psychogenesis and psicoplastía of mental illness and crime.